2013
DOI: 10.4049/jimmunol.1200757
|View full text |Cite
|
Sign up to set email alerts
|

Computational Identification of Antigen-Binding Antibody Fragments

Abstract: Determining which parts of the Ab are essential for Ag recognition and binding is crucial for understanding B cell–mediated immunity. Identification of fragments of Abs that maintain specificity to the Ag will also allow for the development of improved Ab-based therapy and diagnostics. In this article, we show that structural analysis of Ab–Ag complexes reveals which fragments of the Ab may bind the Ag on their own. In particular, it is possible to predict whether a given CDR is likely to bind the Ag as a pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 60 publications
(66 reference statements)
2
21
0
Order By: Relevance
“…This has been shown also for specific examples like the interaction between HyHEL-10 and lysozyme, in which CDRH2 and CDRL1 display a dominant role, while CDRH3 shows very low binding contribution. 38 The fact that CDRH3 is not necessary for the versatility of Abs was ultimately demonstrated by a study that has shown that synthetic libraries can yield specific Abs against different Ags with diverse CDRL3 and fixed CDRH3. 47 In another study, the introduction of diversity into the sequence of anti ErbB2 Ab only at CDRH3 did not result in affinity enhanced variant, while beneficial mutants could be obtained by engineering one of the other contacting CDRs (CDRH1,H2,L1 or L3).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This has been shown also for specific examples like the interaction between HyHEL-10 and lysozyme, in which CDRH2 and CDRL1 display a dominant role, while CDRH3 shows very low binding contribution. 38 The fact that CDRH3 is not necessary for the versatility of Abs was ultimately demonstrated by a study that has shown that synthetic libraries can yield specific Abs against different Ags with diverse CDRL3 and fixed CDRH3. 47 In another study, the introduction of diversity into the sequence of anti ErbB2 Ab only at CDRH3 did not result in affinity enhanced variant, while beneficial mutants could be obtained by engineering one of the other contacting CDRs (CDRH1,H2,L1 or L3).…”
Section: Discussionmentioning
confidence: 99%
“…The CDRs binding contribution may be an important consideration for CDR grafting, Ab humanization, design of 2-in-one Abs and for identifying CDRderived peptides. 38 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is commonly thought that the major contributor to binding and activity of an antibody is the CDR_H3 loop, although we have found exceptions to this generality as have others. 21 Therefore, it would make sense to incorporate changes that introduce beneficial properties distant to CDR_H3 similar to the configuration of mAb_A_42. However, the next 2 most agitation stable and active antibodies included changes to W109 and W110, which were in CDR_H3 as defined by the Kabat CDR definition.…”
Section: Discussionmentioning
confidence: 99%